1998
DOI: 10.1016/s0014-5793(98)00106-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two isoforms of the third sarco/endoplasmic reticulum Ca2+ATPase (SERCA3) in platelets. Possible recognition of the SERCA3b isoform by the PL/IM430 monoclonal antibody1

Abstract: Human platelets express several sarco/endoplasmic reticulum Ca P+ ATPase (SERCA) isoenzymes: SERCA2b of 100 kDa apparent molecular mass and two distinct enzymes of 97 kDa, one of them identified as being the SERCA3a isoform. The molecular identity of the third enzyme specifically recognized by the PL/IM430 monoclonal antibody has remained elusive. First, the study of the 3P-end part of platelet SERCA3 mRNA, by means of RT-PCR amplification using sets of primers covering the N33 to N (ultimate) exons of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Moreover, unfortunately, no information can be expected from rat or mouse, because of their striking differences at least in the nature of their platelet SERCA3 [22,23] and levels of SERCA2b-protein expression [57]. However, it was recently found that the temporal patterns of Ca# + signals depend critically on the SERCA2 isoforms [58] or on the set of InsP $ -R subtypes [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, unfortunately, no information can be expected from rat or mouse, because of their striking differences at least in the nature of their platelet SERCA3 [22,23] and levels of SERCA2b-protein expression [57]. However, it was recently found that the temporal patterns of Ca# + signals depend critically on the SERCA2 isoforms [58] or on the set of InsP $ -R subtypes [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although some controversy exists concerning the expression of InsP $ -Rs, human platelets were reported to express either InsP $ -RI and II or InsP $ -RI and III. About SERCAs, platelets account for the first cells shown to simultaneously express the ubiquitous SERCA2b [18] and SERCA3a proteins [19][20][21] as well as SERCA3b [22] and SERCA3c [23] mRNAs.…”
Section: Three Types Of Inspmentioning
confidence: 99%
See 2 more Smart Citations
“…At 14 days post-coitum it disappears from the heart tube and is present in the dorsal aorta and as small foci in the liver (10). Several groups (12)(13)(14)(15) 2 have recently identified multiple SERCA3 isoforms generated by alternative splicing, and the respective functions of these isoforms are still unknown.…”
mentioning
confidence: 99%